Organizational Politics, Ethical Leadership, and Organizational Citizenship Behavior of Faith-based Institutions in Northern Mindanao Philippines - Rubie C. Cabasag; Efren J. Barillo (PT Mattawang Mediatama Solution, 2024)
Investigating political strategies, ethical concerns, and organizational citizenship is imperative for research. This study determined the level of organizational politics, ethical leadership, and organizational citizenship behavior at faith-based institutions in Northern Mindanao. The descriptive-correlational research design was used in the study, 132 employees as respondents and were selected through purposive and quota sampling techniques. Adapted and modified Organizational Politics, Ethical Leadership, and Organizational Citizenship Behavior Questionnaires were used in gathering the data that were analyzed using Mean and Standard Deviation as well as Pearson Product-Moment Correlation Coefficient to measure the levels of organizational politics, ethical leadership, and organizational citizenship behavior among respondents and explore the significant relationships between these variables. Results revealed that respondents have a low level of organizational politics, a high level of perceived ethical leadership, and a very high level of Organizational Citizenship behavior. Organizational politics was not associated with organizational citizenship behavior. However, ethical leadership was highly significant in organizational citizenship behavior. The study concluded that the ethical behavior and moral conduct of leaders influenced Organizational Citizenship Behavior. Thus, it is recommended that organizations cultivate a moral culture among leaders and managers to elevate Organizational Citizenship behavior in the workplace.